NEET as an Outcome for Care Leavers in South Africa: The Case of Girls and Boys Town. Issue 1 (February 2020) - Dickens, Lisa; Marx, Peter
A well-documented outcome for emerging adults in determining their "success" is whether they are Not in Employment, Education, or Training (NEET) or engaged in Education, Employment, and Training (EET). Being NEET can create psychological, emotional, financial, and health challenges and is a significant risk factor in youth making successful transitions into adulthood. This article describes and compares the NEET and EET status of care leavers from Girls and Boys Town after 1 and 2 years and in relation to other outcomes. The results suggest that while care leavers' NEET rates are high, they are not significantly higher than those of the South African general population as seen elsewhere in the world. Furthermore, being NEET is associated with more negative care leaving outcomes than being EET; however, this article also highlights the vulnerability of those who are EET. Relationships with family and support networks play a critical role in helping and supporting these youth.